2014
DOI: 10.1155/2014/701498
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Electron Enhancements below the Radiation Belt and X-Ray Contamination at Low-Orbiting Satellites

Abstract: The work concerns a problem of electron-induced contaminant at relatively low latitudes to high-energy astrophysical measurements on board the low-orbiting satellites. We show the results of a statistical analysis of the energetic electron enhancements in energy range 30-300 keV observed by a fleet of NOAA/POES low-orbiting satellites over the time period from 1999 to 2012. We demonstrate geographical distributions of great and moderate long-lasting enhancements caused by different type of the solar wind drive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A notable feature of the 22 July storm is a long persistence of FEEs lasting for about several hours. Suvorova et al [] reported that the significant and long‐time enhancement of quasi‐trapped electrons is not an exceptional event for moderate storms. During solar minimum, they can occur regularly as well as recurrent CIR/HSS storms.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A notable feature of the 22 July storm is a long persistence of FEEs lasting for about several hours. Suvorova et al [] reported that the significant and long‐time enhancement of quasi‐trapped electrons is not an exceptional event for moderate storms. During solar minimum, they can occur regularly as well as recurrent CIR/HSS storms.…”
Section: Discussion and Summarymentioning
confidence: 99%